The monitoring system of corporative informational net - Ivchenko, Yu. M.; Ivchenko, V. H.; Hondar, O. M. (Science and Transport Progress, 2011)
The danger of failures of services and divisions of the corporate information-telecommunication system of Prydniprovs’ka Railway, the importance of realization of permanent control of functioning the basic components of a system are estimated in the article. The classification of system components by categories, depending on the functional setting and the software for controlling the сomponents of every category are offered.